Cybervictimization, Social, and Financial Strains Influence Internet Trolling Behaviors: A General Strain Theory Perspective. (June 2023) - Wilson, Nigel C.; Seigfried-Spellar, Kathryn C.
Internet trolling is a form of online aggression that can have negative psychological effects on its victims. This study examines whether Internet trolling behaviors is related to general strain theory. Respondents were solicited from Mechanical Turk and completed an anonymous, Internet-based survey measuring a variety of trolling behaviors and strains (i.e., cyberbullying victimization, trolling victimization, financial strain, and social strain). Of the 259 respondents, 55% self-reported engaging in Internet trolling behaviors. Partial correlations, controlling for sex and age, suggested trolling was significantly related to cyberbullying victimization, trolling victimization, financial strain, and social strain. The hierarchical (blockwise entry) logistic regression found trolls scored higher on cyberbullying victimization, trolling victimization, and financial strain compared to non-trolls. In addition, there was a marginally significant relationship between trolling and higher scores on social strain. Men were also more likely to engage in trolling behaviors compared to women. We conclude there is a relationship between online trolling behaviors and general strain theory. Future research should consider other sources of strain and comparisons between the different types of trolling behaviors (e.g., flaming, griefing, and memorial page trolling) when examining the relationship between trolling and strains. Additional future research suggestions and study limitations are discussed.